2021
DOI: 10.3390/medicina57060640
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Periodontal Disease: A Systematic Review

Abstract: Background and Objectives: The objective of this study was to evaluate the association between periodontal disease and obstructive sleep apnea syndrome (OSAS). Materials and Methods: Electronic search using PubMed, Scopus, LILACS, and Cochrane library was carried out for randomized controlled trials, cohort, case-control, longitudinal and epidemiological studies on humans published from January 2009 until September 2020. The participants had to be male and female adults who were diagnosed with OSAS either by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…However, longitudinal studies linking OSA to periodontitis have found little evidence, and population sizes are often too small to detect clinically relevant associations. In current studies, there are systematic reviews or meta-analyses on the relationship between OSA and periodontitis [ 25 , 26 ], but so far only one meta-analyses has been published in 2015, focusing on the correlation [ 25 ], and no studies on the incidence of periodontitis in OSA patients. In addition, most reliable and new trial results have been published since 2016.…”
Section: Introductionmentioning
confidence: 99%
“…However, longitudinal studies linking OSA to periodontitis have found little evidence, and population sizes are often too small to detect clinically relevant associations. In current studies, there are systematic reviews or meta-analyses on the relationship between OSA and periodontitis [ 25 , 26 ], but so far only one meta-analyses has been published in 2015, focusing on the correlation [ 25 ], and no studies on the incidence of periodontitis in OSA patients. In addition, most reliable and new trial results have been published since 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Nizam et al suggest that OSAS has a key role in the development of periodontal inflammation, with bacterial population changes in the subgingival plaque and an increase in salivary concentration of IL-6 and apeline [ 19 ]. Consequently, a possible link between periodontitis and OSAS has been hypothesized, although the pathophysiological mechanism and cause–effect still remain unclear [ 20 ]. For several years, the dentist has represented an important figure as a diagnostic sentinel, and—along with sleep medicine specialists—had a key role in its therapeutical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies have shown that there appears to be low evidence for the association between OSAHS and periodontitis [ 23 ], and the pathophysiological mechanisms underlying the association between the two conditions remain unclear. We hypothesized that there is a possible correlation between OSAHS and periodontal disease.…”
Section: Introductionmentioning
confidence: 99%